2010
DOI: 10.1590/s1519-566x2010000600028
|View full text |Cite
|
Sign up to set email alerts
|

Sand flies (Diptera: Psychodidae) in a cerrado area of the Maranhão state, Brazil

Abstract: -The present paper aims to increase the knowledge on the sand fl y fauna in the cerrado areas of Maranhão state in urban, rural and forest environments. The research was carried out from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
3
7
0
8
Order By: Relevance
“…This demonstrated the capacity of these species to adapt to houses, especially those located next to rain forest fragments. The location with the highest number of specimens caught was the peridomestic area, and this finding corroborates previous studies (BARATA et al, 2005;SILVA et al, 2010). It is important to highlight that in the present study, animal shelters (hen houses, stables and a piggery) were found in peridomestic areas, and their presence may have influenced the number of specimens collected.…”
Section: Discussionsupporting
confidence: 92%
“…This demonstrated the capacity of these species to adapt to houses, especially those located next to rain forest fragments. The location with the highest number of specimens caught was the peridomestic area, and this finding corroborates previous studies (BARATA et al, 2005;SILVA et al, 2010). It is important to highlight that in the present study, animal shelters (hen houses, stables and a piggery) were found in peridomestic areas, and their presence may have influenced the number of specimens collected.…”
Section: Discussionsupporting
confidence: 92%
“…The greater abundance and diversity of phlebotomine sandflies in the peridomicile has been observed in several areas of Brazil [11][12][13][14] . This behavior increases the risk of transmission of the leishmaniases, and it is related to the presence of animals in household surroundings, as well as vegetation and soil type, which might favor the establishment of breeding sites for phlebotomine sandflies 15 .…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 95%
“…Studies have shown a great species richness and abundance of sand flies in the peri‐domicile environments of several municipalities in the State of Maranhão (Silva et al 2010, 2012, 2015, Campos et al 2013, Rebêlo et al 2019). Some of these species are infected with different Leishmania species (Guimarães‐e‐Silva et al 2017, Pereira‐Filho et al 2018, Fonteles et al 2018).…”
Section: Introductionmentioning
confidence: 99%